Euthanasia: Searching for the Full Story Experiences and Insights of Belgian Doctors and Nurses - Devos, Timothy (Springer Nature, 2021)
This open access book has been written by ten Belgian health care professionals, nurses, university professors and doctors specializing in palliative care and ethicists who, together, raise questions concerning the practice of euthanasia. They share their experiences and reflections born out of their confrontation with requests for euthanasia and end-of-life support in a country where euthanasia has been decriminalized since 2002 and is now becoming a trivial topic. Far from evoking any militancy, these stories of life and death present the other side of a reality needs to be evaluated more rigorously. Featuring multidisciplinary perspectives, this though-provoking and original book is intended not only for caregivers but also for anyone who questions the meaning of death and suffering, as well as the impact of a law passed in 2002. Presenting real-world cases and experiences, it highlights the complexity of situations and the consequences of the euthanasia law. This book appeals to palliative care providers, hematologists, oncologists, psychiatrists, nurses and health professionals as well as researchers, academics, policy-makers, and social scientists working in health care. It is also a unique resource for those in countries where the decriminalization of euthanasia is being considered. Sometimes shocking, it focuses on facts and lived experiences to challenge readers and offer insights into euthanasia in Belgium.